Students' Perception on the Training of the Use Edmodo's E-Learning Application Media in Improving Students' English Writing Skill: Survey Research - Candra Hadi Asmara; Amrin Batubara; Rizky Avira Dhea (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2021)
In Education 4.0 a vision of learning will form which will focus on how the sources of learning will be, then where and how students learn, so learning will become more meaningful while the teacher only acts as a facilitator in learning. However, achieving this vision is not easy, because there are still some problems found, related to the lack of use of technology in learning, and the lack of student knowledge in using technology as a support for the success of one learning. Based on the problems, the solution offered is Training of Utilizing Edmodo E-Learning Application Media to Improve Students' English Writing Ability. This research aims to investigate how the students of MA Masyhudiyah perceive the use of Edmodo as a media in English writing skills and how Edmodo helps the students in developing their writing ability. The participants were taken for the analysis as they fall under the Edmodo users. This research study used a quantitative method and a survey design was administered to gather a questionnaire with answers associated with a 5-point Likert scale ranging from strongly agree to strongly disagree. The survey was created using Google Form and was shared among the students through email and other sources. The result of the study shows that incorporating Edmodo enhances both student interest and motivation in English writing ability when particular Edmodo features are employed. The result through the analysis supports that the students have a positive perception using Edmodo is mainly towards for the resources, support and communication such as forum, discussions and also online activities. Students find Edmodo a wonderful and user-friendly social learning platform that enables them to enjoy working on an online class especially in English writing skills.